Assessing the epistemic dimension of people–place relationships for inclusive ecosystem governance - Hakkarainen, Viola; Soini, Katriina; Raymond, Christopher M. (John Wiley & Sons, 2026)
Senses of place scholarship have rarely addressed the epistemic dimension that influences how people perceive, interpret and interact with places through their knowledges. This limits our understanding of subjective stances and possible contestations within ecosystem governance. We develop the concept of epistemic bonding and conceptualise it as the subjective connection to a place that is created through (perceived) knowledge and the process of knowing about a place. We explore its relationship to the established five dimensions of place attachment by using survey data from 306 residents of the High Coast/Kvarken Archipelago UNESCO Natural World Heritage Site in Sweden and Finland. We also assess the relationship between epistemic bonding and views on management practices in each country. The results show that epistemic bonding is strongly correlated with place dependence and identity and is consistently associated with long-term residency and having family history in the area. Higher epistemic bonding indicated a more negative stance towards official nature protection in Finland. By foregrounding epistemic bonding, we emphasise the role of knowledge in forming place bonds. Epistemic bonding can be a useful lens for understanding how individuals respond to environmental decision-making. Focusing on epistemic bonds highlights crucial questions about whose knowledge is recognised and shapes the management of places, as well as how diverse ways of knowing and relating to place influence the perceived inclusivity of ecosystem governance.
Keywords: ecosystem governance; epistemic bonding; epistemic justice; knowledges; place attachment; senses of place